2022
DOI: 10.1111/srt.13163
|View full text |Cite
|
Sign up to set email alerts
|

Digital skin imaging applications, part I: Assessment of image acquisition technique features

Abstract: Background:The rapid adoption of digital skin imaging applications has increased the utilization of smartphone-acquired images in dermatology. While this has enormous potential for scaling the assessment of concerning skin lesions, the insufficient quality of many consumer/patient-taken images can undermine clinical accuracy and potentially harm patients due to lack of diagnostic interpretability. We aim to characterize the current state of digital skin imaging applications and comprehensively assess how image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…Nine reviews [22][23][24][25][28][29][30]36,38] and one systematic review [32]; • Twenty-five papers [21,26,27,31,[33][34][35][40][41][42][43][44][45]48,[50][51][52][53][54][55][56][57][58][59][60].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine reviews [22][23][24][25][28][29][30]36,38] and one systematic review [32]; • Twenty-five papers [21,26,27,31,[33][34][35][40][41][42][43][44][45]48,[50][51][52][53][54][55][56][57][58][59][60].…”
Section: Resultsmentioning
confidence: 99%
“…The search provided 40 components [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] in the three years since the COVID-19 pandemic outbreak (at the date of this study).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a study done in United Kingdom primary care facilities showed enhanced photo quality when patients were educated with the “4 Key Instructions” (Framing—requesting at least one near and one distant image; Flash—educating about the use of flash to enhance image sharpness, emphasizing not to use it too closely; Focus—educating patients to give the camera time to auto-focus; Scale—asking for a comparison like a ruler or a coin) ( 73 ). Among 191 digital applications for skin imaging, 57% included one or more strategies to enhance quality, but it was rare for applications to have more than one ( 80 ). An immediate feedback feature for image quality shows promise, although it is still in the early stages of development ( 81 ).…”
Section: Barriers To Clinical Implementationmentioning
confidence: 99%